Nocturnal torpor by superb fairy-wrens: a key mechanism for reducing winter daily energy expenditure. (28th June 2019) - Romano, Alex B.; Hunt, Anthony; Welbergen, Justin A.; Turbill, Christopher
Abstract : Many passerine birds are small and require a high mass-specific rate of resting energy expenditure, especially in the cold. The energetics of thermoregulation is, therefore, an important aspect of their ecology, yet few studies have quantified thermoregulatory patterns in wild passerines. We used miniature telemetry to record the skin temperature ( T skin ) of free-living superb fairy-wrens ( Malurus cyaneus, 8.6 g; n = 6 birds over N = 7–22 days) and determine the importance of controlled reductions in body temperature during resting to their winter energy budgets. Fairy-wrens routinely exhibited large daily fluctuations in T skin between maxima of 41.9 ± 0.6°C and minima of 30.4 ± 0.7°C, with overall individual minima of 27.4 ± 1.1°C (maximum daily range: 14.7 ± 0.9°C). These results provide strong evidence of nocturnal torpor in this small passerine, which we calculated to provide a 42% reduction in resting metabolic rate at a T a of 5°C compared to active-phase T skin . A capacity for energy-saving torpor has important consequences for understanding the behaviour and life-history ecology of superb fairy-wrens. Moreover, our novel field data suggest that torpor could be more widespread and important than previously thought within passerines, the most diverse order of birds.